Scenario analysis of vehicular emission abatement procedures in Xi'an, China. (15th January 2021) - Song, Hui; Deng, Shun-Xi; Lu, Zhen-Zhen; Li, Jiang-Hao; Ba, Li-Meng; Wang, Jing-Fa; Sun, Zhi-Gang; Li, Guang-Hua; Jiang, Chao; Hao, Yan-Zhao
Abstract: Vehicular emissions contribute significantly to air pollution, and the number of vehicles in use is continuing to rise. Policymakers thus need to formulate vehicular emission reduction policies to improve urban air-quality. This study used different vehicle control scenarios to predict the associated potential of mitigating carbon monoxide (CO), volatile organic compounds (VOCs), nitrogen oxide (NOx ), particulate matter with an aerodynamic diameter less than 2.5 μm (PM2.5 ), and particulate matter with an aerodynamic diameter less than 10 μm (PM10 ) in Xi'an China, in 2020 and 2025. One business-as-usual scenario and six control scenarios were established, and vehicular emission inventory was developed according to each scenario. The results revealed that eliminating high-emission vehicles and optimizing after-treatment devices would effectively reduce vehicular emissions. In addition, increasing the number of alternative fuel vehicles, restraining vehicle use, and restraining the growth of the vehicle population would all have certain effects on CO and VOCs emissions, but the effects would not be significant for NOx, PM2.5, and PM10 . The results also indicated that if all control measures were stringently applied together, emissions of CO, VOCs, NOx, PM2.5, and PM10 would be reduced by 51.66%, 51.58%, 30.19%, 71.12%, and 71.81% in 2020, and 53.55%, 51.44%, 19.09%, 54.88%, and 55.51%, in 2025, respectively. Graphical abstract: Image 1 Highlights: Future vehicle emissions were predicted using six different vehicle control scenarios. Eliminating high-emission vehicle is a more effective measure in the short-term than in long-term. Optimizing and replacing regularly the after-treatment devices is a effective reduction emission strategy. Restraining vehicle use and growth has some reduction emission effect, especially in long-term. Abstract : The summary of the main finding: Eliminating high-emission vehicle and optimizing the after-treatment devices are two effective reduction emission strategies.